PENGARUH PELATIHAN WIRAUSAHA BARU TERHADAP PENGEMBANGAN USAHA JASA SALON KECANTIKAN DI ( BP3W ) PROVINSI JAWA BARAT - Yulia Listianti; Aryani Catur Rahmawati (POLITEKNIK PIKSI GANESHA, 2022)
This research was conducted at the Center for Education and Training in Operations and Entrepreneurship (BP3W) of West Java Province, which aims to determine the correlation between training and business development and also to analyze the influence of new entrepreneurial training on the development of beauty salon services business in the Center for Education and Training in Operation and Entrepreneurship (BP3W) of West Java Province. Respondents from this study were all alumni of beauty salon service entrepreneurial trainees during 2016 who were selected with random sampling techniques. The method used is quantitative with a descriptive approach, which tests correlation using analysis of the sperman rank corelation, and is also done to determine measurement accuracy using tests of validity, reliability, spearman rank cholera test, and coefficient of determination. The results of this study showed a correlation of new entrepreneurial training and beauty salon service business development in the Center for Education and Training in Operation and Entrepreneurship (BP3W) of West Java Province with a correlation coefficient of r_s = 0.793 calculation results showing a coefficient of determination of 62.89%. This shows that the hypothesis is proven, that there is an influence of new entrepreneurial training on the development of beauty salon services business in the Center for Education and Training in Operation and Entrepreneurship (BP3W) of West Java Province.